Reorientation of Indonesian Criminal Policy Based on the Economic Analysis Of Law Approach - CSA Teddy Lesmana (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Indonesias criminal policy seems to only focus on criminalizing action that are considered morally wrong which overrides one of the objectives of the implementation of criminal law, namely the recovery of the consequences of a criminal act and criminal policy in Indonesia does not seemes to care about the consequences arising from handling cases and the consequences of punishment. Hundreds of thousands of people which of course human resources, places and also very large costs. This paper discusses the idea of economic analysis of law in criminal law policy. This paper also discusses the reorientation of Indonesia criminal policies based on economic analysis of law. The research method used is normative juridical, qualitative research method that takes a normative critical attitude from human insight or existence and criticizies legal practige and legal dogamtics. This writing uses document studies, especially researching the laws and regulations as well as relevant books and journals